2006
DOI: 10.1097/01.tp.0000234675.56598.35
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Lentivirus Transduction and Immediate Transplantation of Uncultured Hepatocytes for Treating Hyperbilirubinemic Gunn Rat

Abstract: This work reports the first demonstration of long-term metabolic benefit after rapid transplantation of ex vivo lentivirally tranduced hepatocytes. Therefore, this study demonstrates the therapeutic proof-of-principle and potential of the SLIT approach for treating inherited metabolic liver diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…In this study, the results have shown a lack of toxicity and persistent gene expression lasting at least four months following gene therapy. Successful reports of human hepatocyte genetic correction, using lentiviral vectors, followed by transplantation in the Gunn rat [94] [10,92] and nonhuman primates [82] have been published. These findings confirm the potential feasibility of gene therapy by using lentiviral vectors to treat liver-based inborn errors of metabolism, which are a prerequisite to clinical applications (for review see [93]).…”
Section: Human Ips Cell Therapies For Hereditary Metabolic Liver Disementioning
confidence: 98%
“…In this study, the results have shown a lack of toxicity and persistent gene expression lasting at least four months following gene therapy. Successful reports of human hepatocyte genetic correction, using lentiviral vectors, followed by transplantation in the Gunn rat [94] [10,92] and nonhuman primates [82] have been published. These findings confirm the potential feasibility of gene therapy by using lentiviral vectors to treat liver-based inborn errors of metabolism, which are a prerequisite to clinical applications (for review see [93]).…”
Section: Human Ips Cell Therapies For Hereditary Metabolic Liver Disementioning
confidence: 98%
“…This transduction was maintained for up to 4 months after injection in the study animals [70] . In addition, the lentiviral vectors were able to transduce a wide range of post-mitotic organs such as muscle [71] , retina [72] , neurons [73] and liver [74] .…”
Section: Lentivirusmentioning
confidence: 99%
“…65 Titers of LV preparations were thus calculated as the number of transducing units per ml. The same qPCR assay was used to determine copy numbers of integrated LV in stably transduced Huh7 and HepG2.2.15 cells.…”
Section: Cell Culturementioning
confidence: 99%